Geodiversity Inventory and Scientific Value Evaluation of Southern Binongko Island in Wakatobi Regency - Masri, Masri; Asruddin, La Ode; Ngkoimani, La Ode (Badan Geologi, 2024)
Binongko Island is one of the largest islands in Wakatobi Regency, Southeast Sulawesi, with unspoiled and exotic natural tourism. Several tourism objects are karstification products from the Ambeua Formation (Tmpa) and Quaternary (Qpl) limestone. To determine the potential of geodiversity on the island, an inventory and scientific value assessment were conducted. This paper presents the results of the inventory and evaluation of geological diversity as a potential geological heritage on Southern Binongko Island. The methods involve field geological mapping and laboratory analysis.. Field geological mapping include geological trajectory planning, lithology data collection, cave geometry descriptions, and preparation of geological diversity inventory matrices. Laboratory analysis includes observing the thin section using microscope polarization. The geomorphological units of the study area can be divided into karst hills and karst plains. Petrographic analysis of nine thin sections showed crystalline limestone units, grainstone, packstone, wackestone, and mudstone—geological structures in limestone terraces with different lithological variations. The geological diversity of the study area is divided into groups of endokarst cave, karst hills, beaches, and limestone terraces which are divided into 11 (eleven) geological sites, i.e., Topa Raja Cave, Topa Lemali Cave, Topa Lembuko Cave, Wa Ode Goa Cave, Yoro Beach, Koncu Patua Wali Hill, Mbara-mbara Beach, La Sikori Cave, Rock Park, La Handu Hill, and Wa Cimbaumba Beach. Geological sites in the study area have medium to high values.The comparison is based on the criteria of geological heritage (geoheritage); the research area is ranked nationally,with a low, medium, and high scientific value. The highest scientific value is in the Taman Batu geosite and KoncuPatua Wali Hills. Three geotracks are recommended: cave geotrack, rock garden hill geotrack, and beach geotrack.